Productive-territorial restructuring in Mato Grosso do Sul, Brazil: observations from the implementation of Suzano Papel e Celulose in Ribas do Rio Pardo (2021-2023) - Delcol, Rafaela Fabiana Ribeiro; Heimbach , Samuel da Silva (Geografares, 2024)
This work aims at analyzing the productive-territorial reconfiguration in Mato Grosso do Sul, mainly in Ribas do Rio Pardo since the establishment of Suzano Papel e Celulose in 2021. Since 1970, the insertion of eucalyptus culture in the state have been experiencing significant changes in the territory planted by eucalyptus, especially in the municipalities that housed, in addition to planting areas, their industrial units. In order to understand the productive-territorial reconfiguration in Ribas do Rio Pardo in the state of Mato Grosso do Sul, the methodological procedures adopted here are based on bibliographic review, field work, primary and secondary data analysis. The results point out transformations in the economic, political and demographic scenario, and show that the manner the city and the countryside were produced have been reconfigured on the basis of the demands of the pulp company and the industrial capital, now that they are subjected to a new way of production which meets the needs of the company and the industrial capital.
Keywords: productive-territorial reconfiguration; Suzano Papel e Celulose; Ribas do Rio Pardo/MS